2024
DOI: 10.1039/d3qm00793f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in transition metal phosphide-based heterostructure electrocatalysts for the oxygen evolution reaction

Wangzhi Wu,
Shuiping Luo,
Yujin Huang
et al.

Abstract: This paper reviews the recent advances in transition metal phosphide-based heterostructure electrocatalysts for the oxygen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 142 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…S15b2†). 54–56 Furthermore, a linear scanning of EDS on the (MnNiCuCoZn)F 2 -PCNFs after the OER also revealed that a distinct high-intensity signal of the oxygen element at the crystal interfaces of the polycrystalline (MnNiCuCoZn)F 2 particles can be realized (Fig. S15d†).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…S15b2†). 54–56 Furthermore, a linear scanning of EDS on the (MnNiCuCoZn)F 2 -PCNFs after the OER also revealed that a distinct high-intensity signal of the oxygen element at the crystal interfaces of the polycrystalline (MnNiCuCoZn)F 2 particles can be realized (Fig. S15d†).…”
Section: Resultsmentioning
confidence: 93%
“…S1a and b †). [54][55][56] For exploring the reasons for the formation of the polycrystalline structure, the melting and boiling points of various related substances have been compiled according to the Lange's Handbook of Chemistry 42 as shown in Table S1 †. The melting and boiling points of each metal uoride are lower than the corresponding carbonization temperature.…”
Section: Resultsmentioning
confidence: 99%